2021
DOI: 10.22599/bioj.164
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the First Peak of the COVID-19 Pandemic on a Paediatric Ophthalmology Service in the United Kingdom: Experience from Alder Hey Children’s Hospital

Abstract: Objective: The COVID-19 pandemic has led to significant service loss across the NHS, and ophthalmology is one of the greatest affected specialties. We attempt to quantify the impact of the first peak of the COVID-19 pandemic on a paediatric ophthalmology unit in a children's hospital in the United Kingdom (UK) and report lessons learnt to aid in the recovery of the service. Methods and Analysis:Two eight-week periods of clinical activity were compared; one during the first UK peak of the COVID-19 pandemic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
(11 reference statements)
1
6
0
Order By: Relevance
“…This study of four months period reported that there was decline in the children attending the hospital by 84%. Similar reduction was seen in the study by Kausher et al [2,4] . In urban areas of Birgunj, with the start of lockdown all the school, playground, parks were closed and gathering of children were stopped.…”
Section: Discussionsupporting
confidence: 88%
“…This study of four months period reported that there was decline in the children attending the hospital by 84%. Similar reduction was seen in the study by Kausher et al [2,4] . In urban areas of Birgunj, with the start of lockdown all the school, playground, parks were closed and gathering of children were stopped.…”
Section: Discussionsupporting
confidence: 88%
“…Reports from USA demonstrated that ophthalmology was the specialty with the largest decrease in outpatient visits, reducing by 79-81% in April/May 2020 (27,28). Similar decreases in ophthalmology attendances were reported as far a eld as UK, Spain, Israel, Italy, Canada and New Zealand (29)(30)(31)(32)(33)(34)(35), although the greatest concern was that sight-threatening cases were presenting later and with worse visual acuities than previous years or simply not presenting to a clinician at all; suggesting fear of vision loss was less than fear of attending hospital during the rst peak of the pandemic (23,30).…”
Section: Discussionmentioning
confidence: 55%
“…[ 5 ] A similar impact was observed on outpatient referrals to a pediatric ophthalmology service in UK which was reduced by 50.2%. [ 6 ] In this study, the most reduction was from the outpatient department (by 66.6%), which is expected due to reduced patient volumes booked in outpatient clinics. However, numerous studies confirmed the largest fall to be from the ED, which in our study was 50.6% reduction in ED referrals alone.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, most of our population from the young pediatric age group, we assume, will be difficult to assess remotely and still require a face-to-face assessment. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%